UTILIZATION OF PERMANENT MAGNET TO REDUCE FRICTION ON VERTICAL AXIS WIND TURBINE BEARING - SANJAYA KALIANDA (NIM : 13106001); Pembimbing Utama : Prof. Dr. Ir. T. A. Fauzi Soelaiman, EKA
Wind energy is one of the renewable energy resources. An alternative to solve the world’s energy crisis problem is to develop wind turbine technology. Wind turbine technology uses energy from the wind to turn the turbine’s blade. The energy absorbed from the blade is converted into mechanical energy, which is then transformed into electrical energy by using a generator. The electrical output from the wind turbine system can be used for various uses. The mechanical friction occurs in the wind turbine bearing causes the wind energy not optimally converted into mechanical energy. The mechanical friction is caused by bearing load that comes from the weight of the wind turbine. Levitation from permanent magnet repulsion force can be used to reduce mechanical friction in vertical axis wind turbine bearing by levitating the turbine. The first step of this research is finding a way to predict the levitating force that comes from the permanent magnet. Validating step is used to calculate the error of prediction method from the actual condition. The validating results show that ANSYS 12 and K&J Magnetics Online calculator are sufficient to predict the levitating force from the permanent magnet. The final step of this research is testing the wind turbine with and without the levitating force. The final result shows that magnetic levitation in wind turbine affect the cut-in speed characteristic of wind turbine. The magnetic levitation that comes from ring permanent magnet gives the lower cut-in speed value than the normal value from 4.1 m/s becomes 2.8 m/s. This lower value means that the wind energy can be obtained at a lower wind speed which is suitable with the condition in Indonesia.